Iodine-catalyzed C3-formylation of indoles via C–N bond cleavage of tertiary amines under aerobic conditions. Issue 22 (3rd June 2015) - Lu, Lin; Xiong, Qiheng; Guo, Shengmei; He, Tianqiang; Xu, Feng; Gong, Jiuhan; Zhu, Zheng; Cai, Hu
Abstract: A novel route was developed for the C3-formation of indoles using iodine as the catalyst. This transformation involves the cleavage of the C–N bond of tertiary amines by the Cross-Dehydrogenative Coupling reaction (CDC), and is well tolerated by a range of 1 H -indoles under aerobic conditions. Moreover, this method can be applied to gram-scale synthesis. Graphical abstract: